(untitled) (Research, Society and Development, 2020)
The social distancing decreed in early 2020 was caused by the high level of contagion of the Covid virus19. Therefore, government, companies and a large portion of Brazilian society were "obliged" to adopt as an alternative to keep active the technological means, among them previously found in industry 4.0. The focus of this research is to raise a reflection on the applicability of technologies as a tool to mitigate the effects of the pandemic in Brazil. In view of the scenario, this article was carried out through bibliographic research, articles, and reports. After the study, it was found that society, in many companies and governments were immersed in to many of the realities of 4.0 technologies, and that they have been, one of the main aids to combat coronavirus and mitigate its effects , which will probably be perpetuated over time whether in a social physical form and / or. It was also observed that the Brazilian reality brings us a reflection for alienation versus the digital exclusion that is found in the same country.